The Potential for Temporary Stand-Off Pads Integrated With Poplar and Willow Silvopastoral Systems for Managing Nitrogen Leaching - Esperschuetz, Juergen; Bloomberg, Mark (Frontiers in Sustainable Food Systems, 2022)
Intensive pastoral farming has been linked to adverse environmental effects such as soil degradation and increased fluxes of nitrogen, phosphorus, sediments, and pathogens into waterways, resulting in their degradation. Stand-off pads are engineered structures covered with bedding materials, available for occupation by stock to minimise those adverse effects to soil and water bodies. Wood chips are ideal for bedding due to their low cost, high water holding capacity, and stock preference as resting areas. While they reduce the mobility of both nutrients and pathogens, their effectiveness depends on the type of wood, size of the chips, pH, pad design, and feeding management used. Dissolved organic carbon, present in wood residue, may slow nitrogen mineralisation thereby decreasing loss via leachate. This effect depends on plant tannins and nutrients already stored within the plant tissue. Poplar and willow have high concentrations of tannins in leaves and bark with potential nitrification-inhibiting properties. When grown on-farm, these deep-rooted trees also reduce nitrogen leaching and prevent soil erosion. This review addresses the use of temporary stand-off pads within poplar or willow silvopastoral systems. Harvested trees can provide suitable wood chips for constructing the stand-off pad, while the deep rooting systems of the trees will reduce the moisture content of the pad, preventing waterlogging. A key objective is to discuss the feasibility and establishment of multiple temporary stand-off pads that allow for stock rotation from pad to pad, and subsequent on-site composting of wood-wastes into fertiliser, reducing both nutrient inputs and losses in agricultural systems. The review highlights the potential suitability of poplar and willow tree species for such a system.